“Cut Prose”? The Sentence and the Line in Marianne Moore’s Poetry - Aurore Clavier (Transatlantica)
This article seeks to examine Marianne Moore’s line breaks and the formal tensions they reveal or even create between the grammatical sentence and the poetical line. While the poet is commonly associated with the most radical and idiosyncratic verse patterns, from her earliest modernist experiments to her signature use of syllabic verse, her work is also marked by a less conspicuous, but equally thorough pull toward the continuity of prose, a genre she was consistently drawn to. Lending an ear and an eye to intervals opened up by these crossings leads to a refined assessment of the generic ambiguities of Moore’s writing.